Effect of pinaverium bromide, trimebutine maleate and cisapride on interdigestive gallbladder volume and postprandial gallbladder emtying in normal subjects - Nadir YÖNETCİ,; Serhat BOR,; A. Ömer ÖZÜTEMİZ,; Hakan YÜCEYAR,; Galip ERSÖZ,; Oktay TEKEŞİN,; Tankut İLTER, (Turkish Journal of Gastroenterology, 2020)
-